Comparison of Biodiesel Properties Produced from Moringa oleifera Seeds Oil and Palm Oil - Ali, Eman N. (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
Biodiesel possess a great potential to help in reducing the dependence on non-renewable fuel which will run out in a near future. Moreover, problems regarding environmental pollution caused from the combustion of fossil fuel and volatile price of this valuable energy had escalated the research and development in production of biodiesel from various feedstocks. The research was conducted to study the effect of different solvent on extracted oil yield, and to compare the properties of biodiesel produced from Moringa oleifera seeds oil and palm oil. The Moringa oleifera seeds were crushed and the oil was extracted by solvent extraction process using three different solvent. The extracted Moringa oleifera oil and palm oil were converted into biodiesel through transesterification process in a presence of methanol and potassium hydroxide as catalyst. As a conclusion, n-Hexane was the best solvent which gives the highest oil yield with an average percentage of 34.3%. The biodiesel properties such as: cetane number was 66.7, 59.5, kinematic viscosity were 4.8 mm2/s, 5.04 mm2/s, cloud point were 18oC, 16oC, pour point 12oC, 7oC, flash point 162oC, 155oC, and density 875 kg/m3, 890 kg/m3 produced from Moringa oleifera seeds oil and palm oil, respectively. Biodiesel produced from Moringa oleifera had a potential to become a better feedstock as it possess a better properties compared to biodiesel produced from palm oil.